Analysis of of Consumer Preferences on Aceh Songket Product Using Conjoint Analysis (Case of Study: Banda Aceh City and Aceh Besar District). Issue 1 (September 2020) - Ilyas,; Zuhri, S; Yusra, E; Maydini, CM; Erwan, F
Abstract: Indonesia as the country rich in cultural heritage, has a variety of characteristics including woven fabric. Songket fabric is one form of woven fabric that is owned by almost every region. Aceh is one of the best producing areas for songket because of its quality. However, the limitations of the songket design made songket fabric not develop as the expectation. Therefore, the innovation is needed based on the consumer preferences by combining songket with other products. This research aims to identify the consumer preferences toward the product. The method that was used to analyze consumer preferences was conjoint analysis. The results showed that there were five attributes that influenced consumers in choosing songket products based on the highest level of importance for each attributes which were basic color at 35, 381%, type of motive at 26, 650%, type of product at 16, 195%, materials at 11, 718% and motive color at 10, 057% while the most preferred combination product based on the highest utility level results from the level of each attributes were clothing product at 0, 089, with black as basic color at 0, 110, gold color as color motive at 0, 012, using polyester and embroidery as materials at 0, 059 and pinto aceh as a motive 0, 089.